NASIONALISME DALAM FILM SURAT KALENG KARYA AZHARI MEUGIT - Rismawati; Wahidah Nasution (Jurnal Metamorfosa, 2020)
This article studies about nationalism in the film Tin Can by Azhari Meugit the directed by Fauzan Santa. The film was published in 2018 with a 1950s film background. This film is known for its nationalism content. The scope of this study covers the doctrine of nationalism in the Film Canned Letter. Nationalism that wants to be seen in this research includes the doctrine of nationalism which means nationalism as an idea, concept, ideas, views, and as an understanding that is realized in the form of autonomy, unity, equality, and national identity. The problem in this study was formulated, namely how is nationalism in the Canned Letter Film by Fauzan Santa? This study utilizes the theory of literary sociology with qualitative methods. The data source of this research is the Canned Letter Film by Fauzan Santa. The data in this study are the doctrines of nationalism in the Canned Letter Film by Fauzan Santa in the form of character dialogue, and also visualization of images that support the study material. The results of this study show that the people of Aceh have nationalism in the form of 1) National autonomy refers to the concepts of freedom and liberation in the form of anti-colonial, participatory in national development, and effectiveness in the implementation of national planning. 2) Unity refers to the concept of ideological unity namely Islam, regional unity, namely Indonesia, and cultural and linguistic unity. 3) The similarity possessed by Aceh and Indonesia is the similarity of determination to achieve independence even though multicultural, but nevertheless there is a similarity of determination, equality of descent, language, region, political unity, customs and traditions, and religion that shape the nationalism of the Acehnese. 4) National identity, namely linguistic identity, Indonesian. Furthermore, other national identities include the President of the Republic of Indonesia, the Indonesian People, and the Indonesian People. Abstrak Artikel ini mengkaji tentang nasionalisme di dalam film Surat Kaleng karya Azhari Meugit ini disutradarai oleh Fauzan Santa. Film ini diterbitkan pada tahun 2018 dengan latar film tahun 1950-an. Film ini dikenal dengan muatan nasionalisme di dalamnya. Ruang lingkup kajian ini meliputi doktrin nasionalisme di dalam Film Surat Kaleng. Nasionalisme yang ingin dilihat dalam penelitian ini meliputi doktrin nasionalisme yang bermakna nasionalisme sebagai ide, konsep, gagasan, pandangan, dan sebagai paham yang terwujud dalam bentuk otonomi, kesatuan, kesamaan, dan identitas nasional. Dirumuskanlah masalah dalam kajian ini, yaitu bagaimanakah nasionalisme dalam Film Surat Kaleng karya Azhari Meugit? Kajian ini memanfaatkan teori sosiologi sastra dengan metode kualitatif. Sumber data penelitian ini adalah Film Surat Kaleng karya Azhari Meugit yang disutradarai oleh Fauzan Santa.Yang menjadi data dalam kajian ini adalah doktrin-doktrin nasionalisme dalam Film Surat Kaleng karya Fauzan Santa dalam bentuk dialog tokoh, dan juga visualisasi gambar yang mendukung pada bahan kajian. Hasil kajian ini menunjukkan masyarakat Aceh memiliki nasionalisme dalam bentuk 1) Otonomi nasional merujuk pada konsep kebebasan dan pembebasan dalam bentuk antikolonial, partisipatif dalam pembangunan Nasional, dan efektifitas dalam pelaksanaan perencanaan nasional. 2) Kesatuan merujuk pada konsep kesatuan ideology yaitu Islam, kesatuan wilayah, yaitu Indonesia, dan kesatuan budaya dan bahasa. 3) Kesamaan yang dimiliki Aceh dan Indonesia adalah kesamaan tekad untuk mencapai kemerdekaan meskipun dari multicultural, namun demikian adanya kesamaan tekad, persamaan keturunan, bahasa, daerah, kesatuan politik, adat-istiadat dan tradisi, serta agama yang membentuk nasionalismenya orang Aceh. 4) Identitas nasional, yaitu identitas kebahasaan, Bahasa Indonesia. Selanjutnya, identitas nasional lainnya antara lain, Presiden RI, Bangsa Indonesia, dan Rakyat Indonesia. Kata Kuci: Film, Nasionalisme, Surat Kaleng